Որոշման ընդունման հատկանիշների համեմատական վերլուծություն - Դուրյան, Մարատ (Զանգակ հրատ.)
The objective of the study included the analysis of methodological approaches to the study of features of decision making in a complex activity, as well as the adaptation and comparative analysis of decision making in the Armenian version of the Melbourne questionnaire decision (MDMQ). Indicators of research performance style decision-making are considered in different groups. Данный этап исследования предполагает анализ методических подходов к изучению особенностей принятия решения в сложных условиях деятельности, а также адаптационный и сравнительный анализ принятия решений в армянской версии вопросника Мельбурна (MDMQ). Рассмотрены и сравнены показатели стилей принятия решений в разных группах.
Keywords: Հոգեբանություն